Inflammation and cancer: friend or foe? - Turizo-Smith, Andrés David; Córdoba-Hernandez, Samantha; Mejía-Guarnizo, Lidy Vannessa; Monroy-Camacho, Paula Stefany; Rodríguez-García, Josefa Antonia (Frontiers in Pharmacology, 2024)
Chronic inflammation plays a crucial role in the onset and progression of pathologies like neurodegenerative and cardiovascular diseases, diabetes, and cancer, since tumor development and chronic inflammation are linked, sharing common signaling pathways. At least 20% of breast and colorectal cancers are associated with chronic inflammation triggered by infections, irritants, or autoimmune diseases. Obesity, chronic inflammation, and cancer interconnection underscore the importance of population-based interventions in maintaining healthy body weight, to disrupt this axis. Given that the dietary inflammatory index is correlated with an increased risk of cancer, adopting an anti-inflammatory diet supplemented with nutraceuticals may be useful for cancer prevention. Natural products and their derivatives offer promising antitumor activity with favorable adverse effect profiles; however, the development of natural bioactive drugs is challenging due to their variability and complexity, requiring rigorous research processes. It has been shown that combining anti-inflammatory products, such as non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, and statins, with plant-derived products demonstrate clinical utility as accessible adjuvants to traditional therapeutic approaches, with known safety profiles. Pharmacological approaches targeting multiple proteins involved in inflammation and cancer pathogenesis emerge as a particularly promising option. Given the systemic and multifactorial nature of inflammation, comprehensive strategies are essential for long term success in cancer therapy. To gain insights into carcinogenic phenomena and discover diagnostic or clinically relevant biomarkers, is pivotal to understand genetic variability, environmental exposure, dietary habits, and TME composition, to establish therapeutic approaches based on molecular and genetic analysis. Furthermore, the use of endocannabinoid, cannabinoid, and prostamide-type compounds as potential therapeutic targets or biomarkers requires further investigation. This review aims to elucidate the role of specific etiological agents and mediators contributing to persistent inflammatory reactions in tumor development. It explores potential therapeutic strategies for cancer treatment, emphasizing the urgent need for cost-effective approaches to address cancer-associated inflammation.